Pronounced Northwest African Monsoon Discharge During the Mid- to Late Holocene - Höpker, Sebastian N.; Wu, Henry C.; Müller, Peter; Barusseau, Jean-Paul; Vernet, Robert; Lucassen, Friedrich; Kasemann, Simone A.; Westphal, Hildegard (Frontiers in Earth Science, 2019)
The mid- to late Holocene aridification pattern of NW Africa remains a matter of controversial debate. While many marine climate reconstructions indicate a relatively abrupt aridification at ~5.5 ka BP, terrestrial palaeoclimate records rather show a spatially and temporally heterogeneous transition towards the modern arid state. To bridge conflicting evidence, we analysed high-resolution (sub-seasonal) ontogenetic oxygen isotope (δ18O) records and bulk 87Sr/86Sr ratios of bivalve shells and fish otoliths of estuarine-associated species. Samples were excavated from archaeological deposits formed during the mid- to late Holocene in a large palaeo-estuary east of the Banc d’Arguin, Mauritania. The mid-Holocene (~5.2 ka BP) δ18O records indicated unrealistically high water temperatures when assuming a modern value for δ18OSeawater, suggesting a substantial input of isotopically lighter water to the study area. Respective salinity estimates consistently indicated persistent monsoonal discharge. Moreover, 87Sr/86Sr ratios of bivalve shells deviated considerably from the rather stable global seawater composition, further supporting the presence of significant terrestrial runoff between 5.0 and 5.3 ka BP. Altogether, our results support doubts regarding an abrupt termination of the African Humid Period in the coastal areas of NW Africa, and show that fully marine conditions were established along the Banc d’Arguin by ~3.0 ka BP.